Mastering Your PhD Survival and Success in the Doctoral Years and Beyond - Gosling, Patricia; Noordam, Lambertus D.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
"Mastering Your PhD: Survival and Success in the Doctoral Years and Beyond" helps guide PhD students through their graduate student years. Filled with practical advice on getting started, communicating with your supervisor, staying the course, and planning for the future, this book is a handy guide for graduate students who need that extra bit of help getting started and making it through. While mainly directed at PhD students in the sciences, the book's scope is broad enough to encompass the obstacles and hurdles that almost all PhD students face during their doctoral training. Who should read this book? Students of the physical and life sciences, computer science, math, and medicine who are thinking about entering a PhD programme; doctoral students at the beginning of their research; and any graduate student who is feeling frustrated and stuck. It's never too early -- or too late! This second edition contains a variety of new material, including additional chapters on how to communicate better with your supervisor, dealing with difficult people, how to find a mentor, and new chapters on your next career step, once you have your coveted doctoral degree in hand.
Preface -- Choosing a Research Group: Pluses and Pitfalls -- Getting Started -- Setting Goals and Objections -- How to Think Like a Scientist -- Designing Good Experiments -- Charting your Progress Month by Month -- Dealing with Setbacks -- Mentors, Leadership and Community -- How to Get Along with Your Labmates, et al -- Group dynamics: Dealing with Difficult Colleagues -- The Art of Good Communication -- Mastering Presentations & Group Meetings -- Searching the Scientific Literature -- Your First International Conference -- From Data to Manuscript: Writing scientific papers that shine -- Celebrate your Success -- How to Make the Best of your Annual Evaluation -- The Final Year: Countdown to your Thesis Defense -- Writing your Doctoral Thesis with Style -- The Final Act: Defending your Thesis with Panache -- Putting it all Together: A PhD. . .So What$1 (Bs Next? -- Is Industry Right for You? Opportunities to Explore -- Exploring Non-Profit Organizations -- Lessons Learned.s
Keywords: Science (General).; Astronomy; Mathematics; Medicine; Life sciences; Popular Science; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Popular Science in Astronomy; Popular Science in Medicine and Health; Popular Science in Nature and Environment; Science, general